2006
DOI: 10.1111/j.1440-1754.2006.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antireflux medication, placebo and infant mental health intervention on persistent crying: A randomized clinical trial

Abstract: Antireflux medications and IMHC were not superior to placebo in treating infants with persistent crying. Although the reduction in maternal distress was similar in all treatment groups, the individualized IMHC reduced the need for subsequent admission to a mother-infant unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
2
41
0
3
Order By: Relevance
“…GERD symptoms decreased in both groups. These results are similar to those of previous studies, which showed similar reduction of GERD symptoms regardless of whether infants were treated with antireflux medication, feeding modification, hypoallergenic formula, maternal counseling, or placebo (Jordan et al, 2006;Moore et al, 2003;Orenstein et al, 2009;Winter et al, 2010). Other studies have suggested that a variety of treatments, including extra attention given to mothers for study purposes (placebo), may lessen GERD symptoms, and a combination of treatments may be more effective than any single treatment (Neu, Corwin, Lareau, & Marcheggiani-Howard, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…GERD symptoms decreased in both groups. These results are similar to those of previous studies, which showed similar reduction of GERD symptoms regardless of whether infants were treated with antireflux medication, feeding modification, hypoallergenic formula, maternal counseling, or placebo (Jordan et al, 2006;Moore et al, 2003;Orenstein et al, 2009;Winter et al, 2010). Other studies have suggested that a variety of treatments, including extra attention given to mothers for study purposes (placebo), may lessen GERD symptoms, and a combination of treatments may be more effective than any single treatment (Neu, Corwin, Lareau, & Marcheggiani-Howard, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Jordan et al found that 22.8% of irritable infants had a reflux index (RI) (percentage of total time the esophageal pH is less than 4) ≥ 10%[17]. Heine et al reported that 4.2% of irritable infants under 3 months of age had a RI ≥ 10% while 21.7% of infants three months and older did[18].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary treatment with amino acid-based formula has also been described as useful in severe colic 122. However, the etiology in most cases is multifactorial,123 and many treatment modalities (some not part of the allergist armamentarium) can benefit children with colic 124. Colic can be associated with GER and oesophagitis, so overlaps between these conditions of complex and interrelated etiology.…”
Section: Immediate Allergic Reactionsmentioning
confidence: 99%